Succinate Dehydrogenase Deficiency in Pediatric and Adult Gastrointestinal Stromal Tumors - Belinsky, Martin G.; Rink, Lori; von Mehren, Margaret (Frontiers in Oncology, 2013)
Gastrointestinal stromal tumors (GISTs) in adults are generally driven by somatic gain-of-function mutations in KIT or PDGFRA, and biological therapies targeted to these receptor tyrosine kinases comprise part of the treatment regimen for metastatic and inoperable GISTs. A minority (10–15%) of GISTs in adults, along with ∼85% of pediatric GISTs, lacks oncogenic mutations in KIT and PDGFRA. Not surprisingly these wild type (WT) GISTs respond poorly to kinase inhibitor therapy. A subset of WT GISTs shares a set of distinguishing clinical and pathological features, and a flurry of recent reports has convincingly demonstrated shared molecular characteristics. These GISTs have a distinct transcriptional profile including over-expression of the insulin-like growth factor-1 receptor, and exhibit deficiency in the succinate dehydrogenase (SDH) enzyme complex. The latter is often but not always linked to bi-allelic inactivation of SDH subunit genes, particularly SDHA. This review will summarize the molecular, pathological, and clinical connections that link this group of SDH-deficient neoplasms, and offer a view toward understanding the underlying biology of the disease and the therapeutic challenges implicit to this biology.